FACTORS AFFECTING THE EXPORT OF CRUDE PALM OIL INDONESIA - Alfret Reynalto; Ernah Ernah (AGROLAND: The Agricultural Sciences Journal, 2019)
Crude palm oil (CPO) is one of the leading export commodity that has contributed greatly to the Indonesian economy. The majority of CPO production is exported to various destination countries such as India, China, Pakistan, the Netherlands, and Malaysia. The proportion of Indonesian CPO exports was 80-75%, and domestic consumption was only 20-15% of total production. Indonesian CPO exports still show an increasing trend. This study aims to identify the factors that affect Indonesian CPO exports using the data from 2002-2017. This research used the multiple linear regression method of Ordinary Least Square (OLS). The results showed that CPO production, CPO prices in the international market, CPO prices in the domestic market, crude oil prices in the international market, the exchange rate of rupiah, and export rates had a significant effect on Indonesia's CPO export.